PENGARUH KINERJA LULUSAN PGMI IAIN CURUP TERHADAP KEPUASAN KERJA ALUMNI DI SD/MI SE KABUPATEN REJANG LEBONG - Jumira Warlizasusi; Susilawati Susilawati (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
Teachers are planners, implementers, as well as evaluators of learning in the classroom, so students are subjects Â that directly involved in this process to achieve educational goals. One of the educational problems in Indonesia is the low quality of the teachers. As the spear in developing students, teachers are required to have the basic skills that needed as educators, mentors and teachers. The purpose of this study is to determine the influence of alumni performance on the performance satisfaction of Primary School Teacher Education of IAIN Curupâ€™s alumni. The research methodology used is descriptive quantitative with a sample of 60 people, these Primary School Teacher Education alumni spread across several Islamic Elementary Schools or Public Elementary Schools in Rejang Lebong Regency. The results showed that there was a positive influence of alumni performance on alumni performance satisfaction, it is 0.85. This means that the better performance of alumni provides, the higher satisfaction of alumni in Primary School Teacher Education IAIN Curup.